Integrasi Metode Klasik dan Kontemporer dalam Pendidikan Karakter Berbasis Pesantren - Surur, Shobihus; Habibullah, Jumadil Awali (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
This study aims to analyse the implementation of pesantren education in shaping the character of students at Pondok Pesantren Hubbul Qur’an Jombang, emphasising the integration of traditional methods and contemporary approaches. The background of this research is rooted in the challenges of globalisation and digitalisation, which potentially weaken the moral values of the younger generation, requiring pesantren to maintain their relevance as institutions of character education. The study employed a descriptive qualitative design involving 10 participants, consisting of students, carers, and the pesantren leader, selected through purposive sampling. Data were collected over three months through participatory observation, in-depth interviews totalling 20 hours, and documentation. Data analysis was conducted through coding (open, axial, and selective), thematic categorisation, and triangulation of sources and methods. The findings indicate that character formation is developed through five key strategies: habituation of discipline, egalitarian leadership of the kyai, reinforcement of ukhuwah islamiyah, cultivation of ukhuwah wathaniyah, and the synergy of traditional practices with pedagogical innovation. The study concludes that pesantren function not only as religious institutions but also as social laboratories shaping students’ character comprehensively—religious, with integrity, and adaptive to modernity. This research provides both theoretical and practical contributions to the development of pesantren-based character education relevant in the era of globalisation.